ANALISIS PROBLEMATIKA KEPEMIMPINAN PENDIDIKAN DALAM PENGELOLAAN MANAJEMEN KEARSIPAN PADA LEMBAGA PENDIDIKAN - Hanif Aulia Rachmah; Khansa Hilyatul Aulia; Muhammad Rafi Akbar Kurniawan; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the problems of educational leadership in managing archival administration within educational institutions. Effective records management plays a crucial role in supporting orderly, accountable, and sustainable educational administration. However, in practice, several issues persist, including the lack of archival management competence, limited leadership attention to archival systems, and suboptimal use of information technology. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings reveal that the main problems lie in weak leadership roles in planning, organizing, implementing, and supervising archival management. Additionally, limited human resources and infrastructure serve as significant obstacles. Therefore, adaptive, visionary, and innovation-oriented educational leadership is needed to improve the quality of archival management in educational institutions. Keywords: educational leadership, records management, problems, educational institutions